THE HISTORY OF JEWELRY : JOSEPH SAIDIAN & SONS - Childers, Caroline (New York, NY : Tourbillon International, in association with Rizzoli, 2018)
Every piece of jewelry tells a story, and none more so than the exquisite pieces in this book, which have passed through several notable owners before arriving at Joseph Saidian & Sons, an antique jeweler's shop nestled in the Manhattan Art and Antiques Center. Each chapter is centered around a particular piece of jewelry and the way in which it is emblematic: a previous owner, an exemplary design or dominant material. From an array of historic pieces from Van Cleef & Arpels to a discussion of Indian royalty and its relationship with jewelry to pages filled with exquisite pearl jewelry, this book satisfies both the casual fan and the devotee with full-color photographs and informative themed chapters.
Keywords: Joseph Saidian & Sons -- Archives; Jewelry -- Pictorial works; Jewelry -- History -- Pictorial works